2006
DOI: 10.1089/thy.2006.16.273
|View full text |Cite
|
Sign up to set email alerts
|

Action of Topical Thyroid Hormone Analogues on Glucocorticoid-Induced Skin Atrophy in Mice

Abstract: Previously we demonstrated the stimulation of collagen synthesis in triiodothyroacetic acid (TRIAC)-topically treated human and mice. In the present study, we have evaluated the dose response effect of thyroid hormone (TH) analogues and tretinoin on glucocorticoid-induced skin atrophy in a haired mouse model. For this investigation, we treated haired mice twice daily for 7 days with various topically administered doses of TRIAC, triiodothyronine-sodium salt (T(3)-Na), diiodothyroacetic acid (DIAC), 3,5-diiodot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 44 publications
(47 reference statements)
1
10
0
Order By: Relevance
“…Previous studies on mice and humans have confirmed that TRIAC is safe when applied topically to the skin (6)(7)(8).…”
Section: Administered (3)mentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies on mice and humans have confirmed that TRIAC is safe when applied topically to the skin (6)(7)(8).…”
Section: Administered (3)mentioning
confidence: 87%
“…Recent work has highlighted their potential contributions to glucocorticoid-induced skin atrophy and wound repair (3)(4)(5)(6)(7)(8). However, the functions of THs in controlling the balance between cell proliferation and cell differentiation in the skin have proven to be puzzling.…”
Section: Administered (3)mentioning
confidence: 99%
“…TRIAC is a natural metabolite of T 3 with the amino group and methylene group removed from the alanine side chain (26). Previous studies in mice and humans have confirmed that TRIAC is safe when applied topically to the skin (28)(29)(30)(31). Additionally, no significant effect on serum thyroid hormone levels with topical TRIAC was observed (28,30).…”
Section: Introductionmentioning
confidence: 83%
“…However, information relating to the mechanism of action of TH in fibroblasts, especially when it comes to the regulation of collagen production, is limited (22). Studies in mice and humans have shown that topical triiodothyronine (T 3 ) and triiodothyroacetic acid (TRIAC) increase dermal collagen production, epidermal thickness, and dermal proliferation (23)(24)(25)(26)(27)(28)(29). TRIAC is a natural metabolite of T 3 with the amino group and methylene group removed from the alanine side chain (26).…”
Section: Introductionmentioning
confidence: 99%
“…Topical application of TA 3 increases dermal thickness and prevents glucocorticoid-induced skin atrophy in mice and humans (Faergemann et al 2002, Yazdanparast et al 2006a, and stimulates procollagen synthesis and keratinocyte proliferation in human skin (Yazdanparast et al 2004, Zhang et al 2012, but has no beneficial effects on plaque psoriasis (Vahlquist et al 2004). …”
Section: Skinmentioning
confidence: 99%